Indigenous Water Rights in Comparative Law. Issue 3 (November 2020) - Macpherson, Elizabeth
Abstract : At the end of the 2015 Academy Award-winning film The Big Short, which explores the origins of the 2008 Global Financial Crisis, a caption notes that the Wall Street investor protagonist of the film who predicted the collapse of the United States (US) housing market would now be 'focused on one commodity: water'. Water is sometimes described in popular culture as 'the new oil' or 'more valuable than gold'. It is predicted to be the subject of increasing uncertainty, competition, conflict, and even war, as increasing demand from a growing human population and development meets reduced supply as a result of poor management, overuse, and climate change.